Transactional Leadership Style and Perception of Organizational Support as a Determinant of Job Satisfaction - Devy Sofyanty; Vera Agustina Y; Danny Ong; Suwantica (Kusuma Negara Business School, 2021)
This research aims to examine and analyze empirically the influence of transactional leadership styles and perceived organizational support partially or simultaneously on job satisfaction. The research method used quantitative methods while the data collection techniques were carried out through questionnaires, interviews, and observations. The sampling technique used in this research was purposive sampling technique. Subjects in this study amounted to 50 employees at the Ministry of Law and Human Rights of the Republic of Indonesia. The data analysis technique used is multiple linear regression analysis processed using Statistical Package for the Social Sciences (SPSS) software. Based on the research results, the findings are as follows: (1) collectively or simultaneously transactional leadership style and perceived organizational support has a positive and significant influence on employee job satisfaction, (2) partially transactional leadership style has a positive and significant influence on employee job satisfaction; (3) partially perceptions of organizational support has a positive and significant influence on employee job satisfaction. Thus, employee job satisfaction can be increased by increasing transactional leadership styles and perceptions of organizational support.